Superoxide dismutase (SOD) activity in stunted children: Review article - Badrya, Leily; Retno Gunarti, Dwirini; Wulandari, Yohannessa (Institute of Computer Science (IOCS), 2024)
This literature review aims to provide an overview of superoxide dismutase (SOD) activity in stunted children. Method is a literature search was done regarding superoxide dismutase activity in stunting. The literature search utilized PubMed to search for published articles, including clinical trials, case reports, and review articles between 2011 and 2023. The result of stunting is a type of chronic malnutrition caused by long-term malnutrition in children. Malnutrition is the cause of 45% of all deaths in children aged <5 years. Deficiency of macronutrients, especially protein and amino acids, especially leucine and arginine in stunting, can cause a decrease in mTORC1 activation, as a pathway in the body's protein synthesis, especially enzymatic synthesis. Disruption of the mTORC1 pathway due to stunting causes a decrease in the synthesis of enzymatic endogenous antioxidants, especially superoxide dismutase (SOD), followed by an increase in free radical molecules in the body. An imbalance between superoxide dismutase (SOD) and an increase in free radicals in stunted children can create short-term impacts, such as recurrent acute infections. There can also be long-term impacts, namely non-communicable diseases, such as obesity, heart disease, and diabetes mellitus in the future. Conclusion: based on this literature review, it can be concluded that there is a decrease in the synthesis and activity of superoxide dismutase (SOD) found in stunted children.